A passive sampling method for detecting analgesics, psycholeptics, antidepressants and illicit drugs in aquatic environments in the Czech Republic - Fedorova, G; Randak, T; Golovko, O; Kodes, V; Grabicova, K; Grabic, R (The Science of the total environment, 2014)
The goal of this study was to assess the bioavailable concentrations of analgesics, psycholeptics, antidepressants and illicit drugs in the surface waters of the Czech Republic. All of the sampling sites are located within the most important water quality monitoring profiles at the Czech Hydrometeorological Institute. The total concentrations of the compounds ranged from 463 to 6,447 ng POCIS(-1) (Polar Organic Chemical Integrative Sampler). Carbamazepine (196-2,690 ng POCIS(-1)) and tramadol (160-2,250 ng POCIS(-1)) were the most abundant compounds at every site. The most polluted sites were those that received communal wastewater effluent and had a low dilution factor (ratio of wastewater effluent and river flow). The aqueous concentrations of the target compounds were estimated using sampling rate values obtained during a field calibration experiment. Patterns in the aqueous concentrations of the compounds (after back calculation from POCIS extracts) and the POCIS concentrations are different, possibly leading to discrepancies between the toxicity assessments conducted using POCIS extracts and those conducted using grab samples of water from the same location.
Keywords: Analgesics; chemické látky znečišťující vodu; Fresh Water; Substance Abuse Detection; Sampling rate; Wastewater; Antidepressive Agents; Czech Republic; Česká republika; Field calibration; odhalování abúzu drog; odpad tekutý - odstraňování; Psychoactive compounds; zakázané drogy; sladká voda; analgetika; POCIS; Environmental Monitoring; Waste Water; Illicit Drugs; monitorování životního prostředí; odpadní voda; antidepresiva; Surface water; Waste Disposal, Fluid; Water Pollutants, Chemical